Balloon catheter cannulation for route identification and axis stabilization during direct freehand cholangioscopy - Vincent Zimmer (Society of Gastrointestinal Intervention, 2019)
Freehand techniques for direct cholangioscopy access have received little attention, given disappointing initial results and high perceived and/or real technical challenges. However, while pure freehand intubation appears feasible in a significant proportion of individuals, technical advancements and tricks of the trade are being developed. Along these lines, herein I present another rescue technique assisting in freehand access for direct cholangioscopy, the "balloon-catheter-cannulation technique", which may be instrumental in overcoming two major hurdles of the procedure, i.e., stable intubation of the papillary orifice with adequate orientation and scope advancement in the common bile duct vis-à-vis gastric loop formation. To further disseminate direct cholangioscopy in the endoscopy community, technical beyond technological advancements, as for instance dedicated next-generation cholangioscopes, appear essential. Herein, I present a technical case report focussing on the limitations of the pure freehand and relative advantages of the "balloon catheter cannulation-assisted" approach for direct cholangioscopy access.